2020
DOI: 10.1016/j.chest.2020.05.583
|View full text |Cite
|
Sign up to set email alerts
|

First Detection of SARS-CoV-2 by Real-Time Reverse Transcriptase-Polymerase Chain Reaction Assay in Pleural Fluid

Abstract: Coronavirus disease 2019 (COVID-19) is a pandemic infection due to the spread of a novel coronavirus (severe acute respiratory syndrome coronavirus 2), resulting in a wide range of clinical features, from asymptomatic carriers to ARDS. The gold standard for diagnosis is nucleic acid detection by real-time reverse transcriptase-polymerase chain reaction in nasopharyngeal swabs. However, due to limitations in this technique's sensitivity, thoracic imaging plays a crucial, complementary role in diagnostic evaluat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
33
0
4

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(39 citation statements)
references
References 11 publications
2
33
0
4
Order By: Relevance
“…To address this issue, Merindol et al (2020) developed an improved RT-PCR based method for direct SARS-CoV-2 detection, which does not require RNA extraction step and is therefore significantly faster. Another recently developed RT-PCR based method of SARS-CoV-2 detection is reverse transcription loop-mediated isothermal amplification (RT-LAMP) ( Mei et al, 2020 ). Furthermore, a colorimetric detection assay was adapted to RT-LAMP method to increase its throughput.…”
Section: Virus Detection By G-quadruplex Biosensormentioning
confidence: 99%
“…To address this issue, Merindol et al (2020) developed an improved RT-PCR based method for direct SARS-CoV-2 detection, which does not require RNA extraction step and is therefore significantly faster. Another recently developed RT-PCR based method of SARS-CoV-2 detection is reverse transcription loop-mediated isothermal amplification (RT-LAMP) ( Mei et al, 2020 ). Furthermore, a colorimetric detection assay was adapted to RT-LAMP method to increase its throughput.…”
Section: Virus Detection By G-quadruplex Biosensormentioning
confidence: 99%
“…And both, heart failure and pulmonary embolism [ 17 ], in addition to respiratory co-infections [ 18 ], are well-recognized etiologies of pleural effusions. Despite the fact that a certain number of patients may have pleural effusions derived from the preceding causes, SARS-CoV-2 undoubtedly gives rise to fluid formation since it has been detected by reverse-transcriptase polymerase chain reaction in pleural fluid specimens [ 19 , 20 ].…”
mentioning
confidence: 99%
“…Bennet D et al [20] described case report of 61 year old renal transplant patient, who had shown presence of SARS-CoV-2 in plural uid by RT-PCR. SARS-CoV-2 was also detected from pleural uid in study done by Malik MI et al [21] (1 case), Mei F et al [22] (1 case), Baek MS et al [23] (1 case) and Turriziani O et al [24] (3 out of 8 cases). As pleural mesothelial cell expresses DPP4 (CD26) receptor, which plays a role for entry of a virus inside the cell, pleura is target for SARS-CoV-2.…”
Section: Resultsmentioning
confidence: 98%